STUDI NUMERIK PRESSURE DROP PADA SILINDER TANDEM DENGAN PENAMBAHAN SPLITTER PLATE DAN VORTEX GENERATOR DI PENAMPANG SEMPIT - Diastian Vinaya Wijanarko (Otopro, 2021)
The numerical study of pressure drop on a tandem cylinder with the addition of a splitter plate and a vortex generator with the effect of a blockage ratio has been completed. The cross-sectional height and diameter of the cylinder in this study used H= 125 mm and D= 37.5 mm, respectively. The blockage ratio is 30%. The Reynolds number (Re) is 52100 ≤ Re ≤ 156000. The distance between cylinders is 5 to 8, where “s” is the distance from cylinder one to cylinder two. The dimensions of the splitter plate are L=D, L=1,5D, and L=2D where "L" is the length of the splitter plate, while the thickness in this study is 1, 75mm. The dimensions of the vortex generator in this study are used those of Hu, et al. [6]. The angle of the vortex generator is = 350 while the length of the vortex generator is H = 3 mm. All variations of this numerical study were carried out using the URANS (Unsteady Reynold Average Navier Stoke) method with a Reynolds number (Re) 52,100 Re 156,000. The smallest pressure drop value is obtained at the Reynolds number 52.100 for all variations, while the highest Reynolds number is obtained at Re 156.000. the addition of a splitter plate and a vortex generator, gives a higher pressure drop when compared to a circular cylinder.